Extração e caracterização dos ácidos naftênicos do tipo ARN através de técnicas analíticas - Frizzera, Henrique Abreu (2023)
Naphthenic acids are one of many compounds present in petroleum that can cause problems in the production process, such as corrosion, emulsion formation and naphthenic precipitation. This type of precipitation occurs mainly by naphthenate salts of the ARN type. ARNs have four carboxylic ends and a structure that varies from C60 to C80, which interacts with bivalent cations (mainly Ca2+) present in the production water, forming a highly viscous gel that subsequently precipitates. In this work, three ARN extractions from deposits of calcium naphthenates were performed using silica gel extrography. In the three experiments, fractions were obtained and characterized by high resolution analytical techniques, such as NMR de 1H and ESI(-)FT-ICR MS and by FTIR. The data obtained by FT-ICR MS, for the first experiment, showed m/z values compatible with those already known in the literature, indicating the purity of the F-3 fraction with a high percentage of O8[H] and O4[H] classes . The NMR de 1H spectra of the acidic fractions showed the majority presence of hydrogens of the alkyl chain and the absence of aromatic hydrogens in fractions F-1 and F-3 (for experiment 1), F-2.2 (for the second experiment) and F -3.4, F-3.5 and F-3.6 (for the third experiment). For the FTIR results, all highlighted samples show relevant signals compared to the signals obtained in the ARN infrared spectrum. This information indicates that silica gel extrography is a promising technique for isolating ARN acids from naphthenic deposits.